Upaya Meningkatkan Kualitas Sumber Daya Manusia dan Sosialisasi Perpajakan Pada Pelaku UMKM - Rida Ristiyana; Eko Trianto (Jurnal SOLMA, 2023)
Background: The increase in the quantity of MSME business actors must be proportional to the rise in quality. The quality of human resources and tax understanding of MSME business actors in Tangerang Regency is still lacking. This service aims to improve the quality of human resources and knowledge of taxation in MSME actors in Tangerang Regency. Method: The socialization activity involved 34 participants with offline implementation. They are located in Saung Topi Bambu ICHE, Jambe, Tangerang Regency. Implementation methods include the preparatory, implementation, evaluation, and reporting stages. Results: The socialization results showed increased knowledge and understanding of MSME actors in Tangerang Regency related to the quality of human resources and taxes by 11.15%. This means that this socialization can contribute to business actors. Of the 34 participants, only two people did not pass the answer; the rest passed. Conclusion: This post-socialization is expected to increase the potential of business actors to become innovative, creative human resources and develop their businesses in a more advanced and extensive direction. In addition, it is hoped that the awareness and compliance of taxpayers of business actors can continue to be improved and become obedient taxpayers in fulfilling their tax obligations so that tax revenue can be optimal.